Большие надежды: [роман] / Ч. Диккенс - Диккенс Чарлз (Вагриус, 2002)
Экземпляры: ф.5 (2002) / Инвентарный номер: 44412 / Цена: / Сис.шифр: 84(4Вел)-44 / Авт.знак: Д 45 / ГРНТИ: 17.82.31 / ББК: 84(4Вел)-44